Дальние миры в романе Ивана Ефремова Туманность Андромеды - Sääsk, Irina (Studia Rossica Posnaniensia, 2020)
The characters of the rational utopia by Ivan Efremov feel an irrational attraction to distant worlds. This allows us to reveal the relationship between Efremov’s fantasy and the neo–mythological novel of modernism. One of the sources of Efremov’s imagery was the book Agni Yoga, published anonymously in Paris by the Roerichs. Nostalgia for the distant worlds becomes a nostalgia for the free world and the pre-revolutionary past of Russia.